Problem-Based Learning as an Effective Learning Tool in Community Medicine: Initiative in a Private Medical College of a Developing Country - Joseph, Nitin (Indian J Community Med, 2016)
BACKGROUND: Knowledge of community medicine is essential for health care professionals to function as efficient primary health care physicians. Medical students learning Community Medicine as a subject are expected to be competent in critical thinking and generic skills so as to analyze community health problems better. However, current teaching by didactic lectures fails to develop these essential skills. Problem-based learning (PBL) could be an effective strategy in this respect. This study was hence done to compare the academic performance of students who were taught Community Medicine by the PBL method with that of students taught by traditional methods, to assess the generic skills of students taught in a PBL environment and to assess the perception of students toward PBL methodology. MATERIALS AND METHODS: This study was conducted among seventh-semester final-year medical students between June and November 2014. PBL was introduced to a randomly chosen group of students, and their performance in an assessment exam at the end of postings was compared with that of the remaining students. Generic skills and perception toward PBL were also assessed using standardized questionnaires. RESULTS: A total of 77 students took part in the brainstorming session of PBL. The correlation between self-assigned scores of the participants and those assigned by the tutor in the brainstorming session of PBL was significant (r = 0.266, P = 0.05). Out of 54 students who took part in the presentation session, almost all 53 (98.1%) had good perception toward PBL. Demotivational scores were found to be significantly higher among males (P = 0.024). The academic performance of students (P < 0.001) and success rates (P = 0.05) in the examination were higher among students who took part in PBL compared to controls. CONCLUSION: PBL helped improve knowledge of students in comparison to those exposed only to didactic lectures. As PBL enabled students to identify the gaps in their knowledge and enhanced their group functioning and generic skills, we recommend PBL sessions: They would help optimize the training in Community Medicine at medical schools. Good correlation of tutor and self-assessment scores of participants in the brainstorming session suggests that the role of tutors could be restricted to assessment in presentation sessions alone. Demotivation, which hinders group performance in PBL, needs to be corrected by counselling and timely feedback by the tutors.